Moderate and Severe Traumatic Brain Injury: Epidemiologic, Imaging and Neuropathologic Perspectives - McArthur, David L. (Brain Pathol, 2006)
This article examines 3 contexts in which moderate or severe traumatic brain injury can be approached. The epidemiologic background of moderate and severe traumatic brain injury is presented, with particular attention paid to new findings from the study of a national hospital inpatient database. We review aspects of neuroimaging and how new imaging modalities can reveal fine detail about traumatic brain injury. Finally we examine the current state of neuropathologic evaluation of, and recent developments in, understanding of the neural disruptions that occur following traumatic brain injury, together with cellular reactions to these disruptions.